Physical and profile data collected aboard the F.G. Walton Smith during cruise WS0623 in the Gulf of Mexico and North Atlantic Ocean from 2006-10-30 to 2006-11-06 (NCEI Accession 0140564) - Ortner, Peter (NOAA NCEI Environmental Data Archive, 2016)
NCEI Accession 0140564 includes physical and profile data collected aboard the F.G. Walton Smith during cruise WS0623 in the Gulf of Mexico and North Atlantic Ocean from 2006-10-30 to 2006-11-06. These data include CONDUCTIVITY, SALINITY and WATER TEMPERATURE. The instruments used to collect these data include CTD. These data were collected by Peter Ortner of US DOC; NOAA; OAR; Atlantic Oceanographic and Meteorological Laboratory, and by Rosenstiel School of Marine and Atmospheric Science as part of NOAA South Florida Ecosystem Restoration. The Lamont-Doherty Earth Observatory (LDEO) submitted these data to NCEI as part of the NSF sponsored Rolling Deck to Repository (R2R) program.